Antigenic heterogeneity of lipopolysaccharide among Burkholderia pseudomallei clinical isolates. - Anuntagool, N; Aramsri, P; Panichakul, T; Wuthiekanun, V; Kinoshita, R; White, N; Sirisinha, S (2000)
Burkholderia pseudomallei (BP) causes melioidosis, a potentially fatal human infection in the tropics. Clinical isolates from different geographical locations have similar morphological and biochemical characteristics. Although BP has been reported to possess 2 types of lipopolysaccharide (LPS) differing in the chemical structure of their O-polysaccharide (O-PS) component, earlier report demonstrated that the clinical strains exhibited identical LPS moieties. Recently, we reported antigenic similarity between the pathogenic (Ara-) and nonpathogenic (Ara+) biotypes. However, a few clinical isolates showed atypical SDS-PAGE profiles. In this study, LPS from 739 BP isolated from patients and animals in different geographical areas were extracted by proteinase K digestion method. Their SDS-PAGE profiles and their immunoreactivities with patients' sera and monoclonal antibody (MAb) to LPS were analyzed. The isolates showed 3 LPS patterns differing in the number and electrical mobility of bands in silver-stained gel. A majority of BP (711) isolates exhibited identical typical ladder pattern, 21 isolates showed atypical ladder pattern and 7 isolates did not exhibit ladder appearance. However, all LPS preparations exhibited similar endotoxic activity as determined by Limulus amebocyte lysate assay. On the other hand, there were no immunological cross reactivity between typical and atypical LPS, as judged from Western blot against homologous and heterologous sera from melioidosis patients from whom the typical and atypical LPS were isolated. Nevertheless, a Western blot profile of the typical LPS showed some variations when probed with MAb against BP LPS (9D5). Heat-killed bacteria from all LPS groups could similarly activate mouse macrophage cell line to produce nitric oxide (NO) and inducible NO synthase (iNOS).